2010
DOI: 10.1590/s1519-69842010000500002
|View full text |Cite
|
Sign up to set email alerts
|

Epipsammic diatoms in streams influenced by urban pollution, São Carlos, SP, Brazil

Abstract: Epipsammic diatoms have important implications for ecosystem processes in lotic environments. Most of the studies on benthic diatoms concentrate on epilithic diatoms and very little is known about epipsammic diatoms. The objective of this study was to assess epipsammic diatom communities in streams in relation to environmental conditions. Epipsammic diatoms and water quality sampling was done at 7 sites during summer base flow period (2008). Forward stepwise multiple regression and canonical correspondence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
11
0
7
Order By: Relevance
“…However, Eunotia species have rarely been mentioned in studies of trophic states, apart from reports of occurrence in low-nutrient (Gómez and Licursi, 2001) and mesotrophic sites (Stenger-Kovács et al, 2007), and their characterisation as typical of oligosaprobic environments (Patrick and Reimer, 1966). In Brazil, E. bilunaris is also considered indicative of less polluted environments (Lobo et al, 2004a;Bere and Tundisi, 2010). However, Salomoni et al (2006; studied epilithic diatoms in Gravataí River (RS, Brazil) Responses of periphytic diatoms to mechanical removal of Pistia stratiotes L. in a hypereutrophic subtropical reservoir and found the species tolerant of eutrophic conditions and an indicator of organic pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Eunotia species have rarely been mentioned in studies of trophic states, apart from reports of occurrence in low-nutrient (Gómez and Licursi, 2001) and mesotrophic sites (Stenger-Kovács et al, 2007), and their characterisation as typical of oligosaprobic environments (Patrick and Reimer, 1966). In Brazil, E. bilunaris is also considered indicative of less polluted environments (Lobo et al, 2004a;Bere and Tundisi, 2010). However, Salomoni et al (2006; studied epilithic diatoms in Gravataí River (RS, Brazil) Responses of periphytic diatoms to mechanical removal of Pistia stratiotes L. in a hypereutrophic subtropical reservoir and found the species tolerant of eutrophic conditions and an indicator of organic pollution.…”
Section: Discussionmentioning
confidence: 99%
“…palea, which was common in May and November 2008, is commonly cited as an indicator of eutrophic conditions (Lange-Bertalot, 1979;Gómez and Licursi, 2001;Lobo et al, 2004a,b,c;Salomoni et al, 2006;Potapova and Charles, 2007;Stenger-Kovács et al, 2007), ß-mesosaprobic to polysaprobic environments (Salomoni et al, 2011), and polysaprobic environments (Descy, 1979), and is often reported to occur in water with low concentrations of dissolved oxygen (Van Dam, et al, 1994;Hofmann, 1994;Duong et al, 2006). N. palea, like G. parvulum, was considered an indicator of high phosphorus levels in a study that examined a gradient of phosphorus concentrations in a protected area in Florida (Cooper et al, 1999) and highly polluted sites in Brazilian rivers (Bere and Tundisi, 2010). By contrast, Salomoni and Torgan (2008) reported that these species were present in every sample of their study on Guaíba Lake (RS, Brazil) and did not serve as indicator species.…”
Section: Discussionmentioning
confidence: 99%
“…Para o Estado de São Paulo foram encontradas apenas quatro citações da espécie passíveis de reidentificação (Ludwig 1996, Moutinho et al 2007, Bere & Tundisi 2010, Marquardt 2012); e, para o Estado do Paraná, apenas uma (Bertolli et al 2010). É a primeira citação da espécie para a bacia do rio Paranapanema, onde ocorreu apenas à montante do Reservatório de Capivara, distribuindo-se em 7% das estações de amostragem (tabela 1).…”
Section: Figuraunclassified
“…Tavares & Valente-Moreira 2000, Moura & Bittencourt-Oliveira 2004, Procopiak et al 2006, Torgan et al 2009, Tremarin et al 2009, Bertolli et al 2010, Faria et al 2010. No Estado de São Paulo, foi documentada em poucos trabalhos , Bere & Tundisi 2010, sendo dois para a área de estudo, Reservatório de Rosana (Bicudo et al 1993) e rio Tibagi (BittencourtOliveira 2002). Mais recentemente, a distribuição da espécie no Estado de São Paulo foi bastante ampliada por Marquardt (2012).…”
Section: Figuraunclassified
“…En el continente americano, las diatomeas han sido investigadas desde el punto de vista taxonómico (Metzeltin & Lange-Bertalot, 1998;Ponader & Potapova, 2007;Sala, Ramírez, & Plata, 2008;Vouilloud, Sala, Nunez, & Duque, 2010) y como bioindicadoras (Potapova & Charles, 2007;Bere & Tundisi, 2010;2011a;2011b;Tudesque, Grenuillet, Gevrey, Khazraie, & Brosse, 2012). En Costa Rica, se ha estudiado el uso de las diatomeas como indicadoras de diferentes condiciones ambientales (Silva-Benavides, 1996b;Michels, 1996Michels, , 1998a1998b;Michels, Umaña, & Raede, 2006;Nunn, 1999).…”
unclassified